Analisis Asuhan Keperawatan Dengan Intervensi Teknik Buteyko Terhadap Penurunan Kecemasan Dan Frekuensi Pernafasan Asma Bronchial Di Instalasi Gawat Darurat Di RSUD Pasar Minggu - Geofunny Valeryta Dewi (2023)
Asthma is a reversible chronic inflammatory disease of the respiratory tract with typical signs and symptoms such as recurrent shortness of breath, coughing and wheezing, increased respiratory rate (RR) above 30x/minute, use of accessory muscles (chest retraction), widening of the nose, lethargy. , restlessness, cyanosis and dyspnea which cause ineffective breathing patterns and cause impaired oxygen ventilation which can lead to decreased perfusion and oxygen transport in the tissues. There are approximately 235 million people suffering from asthma worldwide and more than 80% of asthma-related deaths in developing countries. There are around 461 thousand cases of death in 2019 caused by asthma attacks each year, with the highest number in countries with low to moderate economies. The purpose of this study was to determine the Analysis of Nursing Care with Buteyko Intervention Techniques for reducing anxiety and respiratory rate in bronchial asthma patients in the emergency room. This study used the Buteyko technique which was carried out approximately 15 minutes after 1 hour of administration of a pharmacological nebulizer. The results of the study showed that there was a decrease in anxiety, respiratory rate, blood pressure, pulse rate and increased oxygen saturation in the emergency room.